Ideal edutech model based on qur’anic perspective (Implementation at the center for education and training of administrative) staff) - Siti Kusriyah (12 Waiheru, 2024)
This Qur’an-based ideal Edutech model research aims to identify the best studies and practices in facilitating learning and improving work performances by creating, using, and managing processes and proper technologies. The research used a qualitative descriptive method as the research method. As for the Qur’anic interpretation method, at-Tafsir al Maudhu’i (thematic interpretation) was used since it is considered capable of addressing contemporary issues and providing a comprehensive perspective of the Qur’an in solving problems that continue to emerge along with the times. The results of satisfaction evaluation and measurement of training participants in 2023 scored 89,56 signifying the improvement after the implementation of Edutech. It showed, through the library research, several ideal models of the implementation of the Qur’an based Education Technology, such as prophet Yusuf model in the implementation of the resilience of Pusdiklat Tenaga Administrasi (The Center for Education and Training of Administrative Staff), and the Quran-based ADDIE model (analysis, design, development, implementation, and evaluation). The advantage of this research lies in Quran-based Edutech, as many verses of the Quran encourage the implementation of innovation and creativity by utilizing technology in education.